Development of a Novel Feedback Filtered Orthogonal Frequency Division Multiplexing Scheme for 5G Network and Beyond - Augustine, Zakka; Tekanyi, A.M.S; Sani, S.M.; Usman, A.D.; A. S. Yaro (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
Previous generations of wireless technologies from 0G through 4G used synchronous data transmission for multiple users, which made it difficult to accommodate recent wireless devices and increasing user demands. The Fifth Generation (5G) network standardized by the year 2020 was designed to harmonize the use of asynchronous transmission.This is to accommodate not only new devices and multiple users,but also different type of users.In this regard, so many mitigation schemes were developed to meet the 5G and 5G-A expectations but suffered one limitation or the other, such as Inter Symbol Interference (ISI), Inter Channel Interference (ICI), Peak to Average Power Ratio (PAPR), and more. Each limitation had serious damaging effect on the performance of the 5Gnetwork because the techniques were not appropriate. Hence, this paper,presenteda novel Feedback Filtered Orthogonal Frequency Division Multiplexing (FF-OFDM) scheme with performance indices of Bit Error Rate (BER) and Signal to Noise Ratio (SNR) in an Additive White Gaussian Noise (AWGN) domainthatprovide solutions to these limitations. Simulation resultsof FF-OFDM showed a 54.4% reduction in the BER and a 17.0% improvement in the SNR,when compared with those ofCyclic Prefix Orthogonal Frequency Division Multiplexing(CP-OFDM) deployed in Long Time Evolution-Advanced(LTE-A) network. FF-OFDM signal waveform which is synonymous to that of Electromagnetic Wave (EMW) because of its orthogonal nature, is systematically designed to mitigate Inter Symbol Interference (ISI), Inter Channel Interference (ICI), and boost processing speed to achieve the 1 ms round trip latency expectation of 5G network and beyond.